2022
DOI: 10.1108/ijse-02-2021-0108
|View full text |Cite
|
Sign up to set email alerts
|

Carbon emissions, inequalities and economic freedom: an empirical investigation in selected South Asian economies

Abstract: PurposeThe purpose of this study is to analyze and empirically test the impact of Economic Freedom [(EF) measured by size of the government] and inequality on environmental pollutants in addition to macroeconomic variables like per capita GDP, governance indicators, etc. along with existence of non-linear (Kuznets) postulation between economic growth and per capita emissions.Design/methodology/approachThe paper examines the select Asian nations' data attributes, first qualitatively using correlation data techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 111 publications
(140 reference statements)
0
10
0
Order By: Relevance
“…The environmental implications of government size can vary greatly between economies (Lan et al, 2022). Recently, Jain and Kaur (2022) found that countries with more EF-compliant institutions and policies experience faster economic growth, greater investment rates, higher income levels, faster poverty reduction, and better air quality. In a comprehensive study, Adewuyi (2016) collected data from 40 of the world's most polluted countries from 1990 to 2015 to examine the effects of government spending on CO 2 emissions.…”
Section: Empirical Literaturementioning
confidence: 99%
“…The environmental implications of government size can vary greatly between economies (Lan et al, 2022). Recently, Jain and Kaur (2022) found that countries with more EF-compliant institutions and policies experience faster economic growth, greater investment rates, higher income levels, faster poverty reduction, and better air quality. In a comprehensive study, Adewuyi (2016) collected data from 40 of the world's most polluted countries from 1990 to 2015 to examine the effects of government spending on CO 2 emissions.…”
Section: Empirical Literaturementioning
confidence: 99%
“…In the related empirical literature, a few scholars have analyzed the interaction between government size and CO 2 emissions. In this context, Jain and Kaur [37] reveal that higher government size (or more market-oriented economies) decrease the CO 2 emissions in Asian economies, but Chen [24] discovers a positive effect of government size on CO 2 emissions in Brazil, China, India, and South Africa in the short and long term and a negative long-term effect of government size on CO 2 emissions in Russia. So, the empirical findings suggest that government size matters for CO 2 emissions for different countries, and our findings are mainly in line with the limited empirical findings.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, Odugbesan et al [14] discovered a positive effect of economic freedom on carbon productivity for Turkey. Cheon et al [34], Adesina and Mwamba [35], Bjørnskov [36], Jain and Kaur [37], and Wood and Herzog [38] revealed a negative influence of economic freedom on CO 2 emissions for different country groups through panel regression analysis. In this context, our findings are in accord with the related empirical literature.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations